1996
DOI: 10.1097/00004836-199606000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Antioxidant, Nitrites, and Mucosal Lipoperoxidation in Chronic Gastritis and Helicobacter pylori Infection

Abstract: We have evaluated gastric juice pH, nitrites and vitamin C levels, mucosal glutathione, and malondialdehyde, a marker of lipid peroxidation, in patients with chronic gastritis undergoing endoscopy. Patients had chronic gastritis with (n = 28) or without (n = 60) atrophy and/or concomitant Helicobacter pylori infection. Nineteen healthy subjects, without major macroscopic or histologic changes, were included as controls. Ten subjects were studied before and after H. pylori eradication. Vitamin C levels were low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 23 publications
6
65
0
1
Order By: Relevance
“…Although vitamin C is locally secreted into gastric juices under physiological conditions, hypochlorhydria, a pH exceeding 4, is associated with lower vitamin C levels in gastric juices (22,23). H. pylori infection is known to decrease vitamin C levels in gastric juices (24,25). Thus, a decrease in vitamin C levels in gastric juices may be one of causes of peptic ulcer development.…”
Section: Discussionmentioning
confidence: 99%
“…Although vitamin C is locally secreted into gastric juices under physiological conditions, hypochlorhydria, a pH exceeding 4, is associated with lower vitamin C levels in gastric juices (22,23). H. pylori infection is known to decrease vitamin C levels in gastric juices (24,25). Thus, a decrease in vitamin C levels in gastric juices may be one of causes of peptic ulcer development.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection is the major contributor to the development of gastric cancer and precancerous gastric lesions in Linqu (15,20,38). H. pylori infection-induced chronic inflammation could cause oxidative stress by producing ROS, including O 2 − (22)(23)(24)(25). It has been shown that H. pylorirelated gastritis is accompanied by an increased oxygen free radical formation and peroxidative damage (22,39).…”
Section: Discussionmentioning
confidence: 99%
“…Because exposure to H. pylori and other risk factors results in an inflammatory reaction and DNA damage of gastric epithelial cells with the generation of ROS (21)(22)(23)(24)(25)(26), and MnSOD is the primary antioxidant enzyme in the mitochondria against ROS, we selected MnSOD as a candidate gene for this study. We investigated the relationship between MnSOD Val 16 Ala polymorphism and the risk of advanced gastric lesions, and the possible interaction between this polymorphism and environmental risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…All of these may cause point mutations in DNA by base substitution and can accumulate, but 8OHdG is considered to be the main DNA modification produced by ROS (18) and consequently is used as an index of damage to the base sequence of DNA (19). HP-related gastritis is characterized by increased free radical production and peroxidative damage (20).…”
Section: Implications Of Antioxidant Enzymes In Human Gastric Neoplasmsmentioning
confidence: 99%